Nanoparticles of Thiolated Xanthan Gum for the Oral Delivery of Miconazole Nitrate: In Vitro and In Vivo Evaluation - Nader I. Namazi; Hamad Alrbyawi; Abdulkareem Ali Alanezi; Afaf F Almuqati; Anwar Shams; Hany S. M. Ali (MDPI AG, 2024)
The objective of this research was to develop a mucoadhesive delivery system that improves permeation for the administration of poorly absorbed oral medications. Thiolation of xanthan gum (XGM) was carried out by esterification with mercaptobutyric acid. Fourier-transformed infrared spectroscopy was used to confirm thiol-derivatization. Using Ellman's technique, it was revealed that the xanthan-mercaptobutyric acid conjugate had 4.7 mM of thiol groups in 2 mg/mL of polymeric solution. Using mucosa of sheep intestine, the mucoadhesive properties of XGM and thiolated xanthan gum (TXGM) nanoparticles were investigated and we found that TXGM had a longer bioadhesion time than XGM. The disulfide link that forms between mucus and thiolated XGM explains why it has better mucoadhesive properties than XGM. A study on in vitro miconazole (MCZ) release using phosphate buffer (pH 6.8) found that TXGM nanoparticles released MCZ more steadily than MCZ dispersion did. A 1-fold increase in the permeation of MCZ was observed from nanoparticles using albino rat intestine compared to MCZ. Albino rats were used to test the pharmacokinetics of MCZ, and the results showed a 4.5-fold increase in bioavailability. In conclusion, the thiolation of XGM enhances its bioavailability, controlled release of MCZ for a long period of time, and mucoadhesive activity.